2021
DOI: 10.31100/histogram.v4i2.726
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Hasil Belajar Berdasarkan Komponen Proses Literasi Matematika

Abstract: Penelitian ini merupakan penelitian kualitatif deskriptif, dengan tujuan untuk mendeskripsikan hasil belajar matematika dilihat berdasarkan komponen proses literasi matematika. Komponen proses merupakan salah satu dari tiga komponen penilaian menurut Program International Student Assesment (PISA). Komponen proses yang diuji dalam penelitian ini meliputi 1) kemampuan merumuskan masalah, 2) kemampuan dalam menggunakan konsep, fakta, prosedur dan penalaran, dan 3) kemampuan menafsirkan hasil. Metode yang digunaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…PISA references in presenting problems using problems that contain context (Lutfianto &;Sari, 2017). PISA problems emphasize students' ability to connect the context of the problem with mathematical concepts in order to obtain solutions from malasah (Rusmining, 2019). The results of the PISA study published by the OECD that assessed mathematical literacy skills showed in table 1.…”
Section: Introductionmentioning
confidence: 99%
“…PISA references in presenting problems using problems that contain context (Lutfianto &;Sari, 2017). PISA problems emphasize students' ability to connect the context of the problem with mathematical concepts in order to obtain solutions from malasah (Rusmining, 2019). The results of the PISA study published by the OECD that assessed mathematical literacy skills showed in table 1.…”
Section: Introductionmentioning
confidence: 99%